2004
DOI: 10.1007/s00595-003-2725-x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Limberg Transposition Flap for Sacrococcygeal Pilonidal Sinus

Abstract: These results provide further evidence that wide excision with a Limberg transposition flap reconstruction is an effective surgical method for primary or recurrent pilonidal sinus, associated with a low complication rate, short hospitalization and disability, and a low recurrence rate. A modification of the technique was devised to further enhance wound healing and reduce the risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
111
2
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 25 publications
7
111
2
18
Order By: Relevance
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 62%
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 62%
“…So, looking that way one expects flap procedures to combat the disease recurrence better than excision with simple closure, keeping in view extensive dissection of the sinus tracts and the shallower cleft that flap procedures provide. Literature has documented a recurrence rate of 0-3% [2][3][4][5][6] for Limberg flap against a significantly high recurrence of 7-42% [7,8] for primary closure. Outcome of our study in terms of recurrence of the sinus is the same as reported by other studies, namely, three recurrences for the primary closure group against zero recurrence of the Limberg flap group.…”
Section: Discussionmentioning
confidence: 99%
“…Aslam had 110 patients, with 5 of them having complications and 1 recurrence [19]. Mentes and Urhan were other studies [20,21]. In our series we had two complex wound infections, three minor flap edemas, and one flap tip discharge-all healed in due time.…”
Section: Discussionmentioning
confidence: 70%